45 The Association between Sensory Impairment and the Incidence of Fall among Indonesian Elderly. (20th December 2019) - Nugraha, Susiana; Hapsari, Indri; Sabarinah,; Pengpid, Supa; Peltzer, Karl
Abstract: Fall is the biggest caused of injury among elderly. It can be markers of poor health and declining function, and they are often associated with significant morbidity moreover it cause disability in the elderly that may increase health funding. The prevalence of fall among elderly in Indonesia is 8.2%. Most of them occur at home and the environment (63.7%), on the highway (18.9%) and the workplace (8.8%) (Ministry of Health Republic Indonesia, 2019). The normal changes of aging, like poor eyesight or poor hearing, considered as the risk of fall among the elderly. This condition has been linked to all-cause of mortality through three mediating variables i.e. disability in walking, cognitive impairment, and self-rated health (WHO, 2007) . This study aimed to assess the association between sensory impairment (hearing impairment and visual impairment) and the incidence of falls among the Indonesian elderly. This study conducted in cross sectional setting. Populations of this study are the elderly from 3 provinces namely Jakarta, West Java and Yogyakarta and selected in cluster random sampling. A total of 427 elderly (those who are above 60 years old) are participated this study. Hearing impairment is evaluated in self-reported and observation and visual acuity test performed to identify the visual impairment. The incidence of fall is identified by self-reported fall in the last 12 months. The multiple regression analysis identifies the model predictor for fall is statistically significant. The result showed that after adjusted to age and gender, elderly with vision impairment likely to have 2.054 times (95%CI 1.265 -3.335) to fall, the elderly with hearing impairment have 1.66 higher odds to fall (95%CI 1, 005 - 2, 793); Male Gender OR =0.46 (95% CI 0, 288 -0, 783) and Ages OR=1.84 (95%CI 1.1.67 -2.894). This finding indicates that after adjusted to ages and gender sensory impairments are increase the risk of fall among Indonesian elderly.